Analisis Faktor Keterlambatan Penyelesaian Proyek Peningkatan Jalan Ruas Ambemali (Studi Kasus Jln. Belalo/Lasolo – Jln. Arisunggu) - Sakti, Putra; Junarto, Junarto (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Delays in implementing construction projects can have negative impacts on contractors and owners. Contractors whose construction projects are late will experience losses in terms of time and costs, because the profits expected by the contractor will be reduced, or even no profits at all. Respondent characteristics based on the questionnaire were classified into several categories, work experience, latest education, company category and field of work in the company. Factors causing delays in work on the Ambemali Road Improvement construction project, Jln. Belalo – Jln. Lasolo, Wawotobi District, Konawe Regency, according to the perception of PPK/PPTK, Directors, Consultants and Service Providers (Contractors) of PT Kendari Baruga Pratama, is caused by Labor Factors with indicators of contractor negligence, Equipment Factors with indicators of Equipment Damage, material factors with this being the lack of material available around the work site , financial factors indicating limited contractor funds, managerial factors namely inappropriate implementation methods, design suitability factors indicating design changes and other factors namely material sources far from the work location.